2001
DOI: 10.1097/00007890-200106270-00016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Immunosuppressive Treatment on Host Responses Against Intracerebral Porcine Neural Tissue Xenografts in Rats

Abstract: Pretreatment of the donor tissue with free-radical scavengers reduces cell loss caused by tissue trauma. Porcine neural tissue xenografts survive significantly better in animals immunosuppressed with either FK or CsA. Additional inductive treatment with PRE or MMF reduced the infiltration of host cells into the xenografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 47 publications
3
14
0
1
Order By: Relevance
“…Conventional immunosuppressive drugs used as monotherapy (e.g., cyclosporin A or tacrolimus) do not protect grafts effectively, [65][66][67] but this can be improved if combined with other drugs such as prednisolone. 65 Short courses of treatment with molecules that block T-cell costimulation [CD40L, LFA1, and CTLA4Ig (40,41)] have resulted in very good graft survival in mice, although long-term studies are needed to determine whether this therapy could be used clinically. 41 The role for humoral factors in xenograft rejection has been addressed using a number of different approaches.…”
Section: Xenogeneic Neural Graftsmentioning
confidence: 99%
“…Conventional immunosuppressive drugs used as monotherapy (e.g., cyclosporin A or tacrolimus) do not protect grafts effectively, [65][66][67] but this can be improved if combined with other drugs such as prednisolone. 65 Short courses of treatment with molecules that block T-cell costimulation [CD40L, LFA1, and CTLA4Ig (40,41)] have resulted in very good graft survival in mice, although long-term studies are needed to determine whether this therapy could be used clinically. 41 The role for humoral factors in xenograft rejection has been addressed using a number of different approaches.…”
Section: Xenogeneic Neural Graftsmentioning
confidence: 99%
“…Despite this, neural xenografts in the brain of untreated recipients are rejected (8,9) with very rare exceptions (10). Studies have shown that a combination of immunosuppressive drugs can be used to overcome the rejection process of porcine xenografts in rats (11,12), but not in mice. No treatment so far has led to any significant graft survival in mice except blocking the costimulatory signals lymphocyte function antigen (LFA)-1 and B7 in CD40L-deficient mice (13).…”
Section: Triple-treated Mice Showed a Normal Rejection Process Of Thementioning
confidence: 99%
“…In a meta-analysis, the rate of neural xenograft survival with cyclosporine A monotherapy was around 75%, but most of the models included in the meta-analysis were concordant [9]. Combinations of immunosuppresssive drugs are more effective [19], but chronic systemic immunosuppression carries risks of opportunistic infections and tumor development. Since Parkinson's disease is not life threatening and the treatment perspective should be very long, a selective short-term immunotherapy would be desirable.…”
Section: Introductionmentioning
confidence: 99%